A theoretical insight into enhancing student intercultural competence: Saudi Arabia as a future business and tourism hub - Alsulami, Nawaf N.; Hashim, Abdel Mohsen Ibrahim; Najmi, Ali Hussein; Alamri, Marai Mohammed; Zamakhshari, Nahla Abdulrahman (Edelweiss Applied Science and Technology, 2025)
This paper provides a theoretical insight into intercultural competence by examining its concept, types, and significance, and by highlighting the urgent need to enhance it in Saudi Arabia—a promising, culturally diverse hub. It emphasizes the importance of improving intercultural competence among Saudi students so they can adapt to the country’s increasingly cross-cultural environment. Drawing on past research, the paper offers future insights into developing intercultural competence and proposes a method for its assessment. The findings are expected to be of significant value to university stakeholders in refining academic programs and institutional practices, ensuring that graduates are well-prepared to compete and thrive in a multicultural and multiethnic global environment.